Peran Universitas dalam Pengelolaan Sampah Menurut Undang-Undang Nomor 18 Tahun 2008 Tentang Pengelolaan Sampah - Abdul Rahmat Waladow (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2024)
This study aims to determine the Role of Universities in Waste Management According to Law Number 18 of 2008 concerning Waste Management. This type of research is Normative Research. The results of the study indicate that waste management is carried out through waste reduction and handling activities (Articles 19-23), and everyone is required to reduce and handle waste in an environmentally friendly manner (Article 12 Paragraph (1). Waste reduction is carried out through 3R activities, namely limiting waste generation (reduce), recycling waste (recycle), and reusing waste (reuse). campuses/universities including all elements and elements in them have duties and obligations in waste management. As a higher education institution, campuses should be able to conduct studies and innovations in waste management. Don't let campuses only become contributors of waste in an area. Campuses or universities must have policies, movements, and innovations in waste management, and are expected to be role models in waste management.